Encryption of 3D Point Cloud Object with Deformed Fringe. (15th February 2016) - Yang, Xin; Zhang, Hongbo
Abstract : A 3D point cloud object encryption method was proposed with this study. With the method, a mapping relationship between 3D coordinates was formulated andZ coordinate was transformed to deformed fringe by a phase coding method. The deformed fringe and gray image were used for encryption and decryption with simulated off-axis digital Fresnel hologram. Results indicated that the proposed method is able to accurately decrypt the coordinates and gray image of the 3D object. The method is also robust against occlusion attacks.